1985
DOI: 10.1037/0022-3514.49.5.1283
|View full text |Cite
|
Sign up to set email alerts
|

The attributional norm of internality and depressive sensitivity to social information.

Abstract: Two studies examined the existence, within an achievement-related context, of a social norm favoring internal explanations for task performances. In the first study, we investigated the reactions of observers to an actor's high, moderate, or low self-attribution of causal responsibility for his negative performance outcome on an ostensibly standardized aptitude test. The results indicated that the actor was evaluated more positively to the degree that he accepted more personal responsibility for his performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 20 publications
2
36
1
Order By: Relevance
“…The social value attached to certain events may be transferred to the persons who bring about such events (or make such judgments), which is what one of the paradigms of the normative approach, the judge paradigm, is able to show. With this paradigm, it has been amply demonstrated that a norm of internality (Beauvois, 1984;Beauvois & Dubois, 1988;Dubois, 1994;Jellison & Green, 1981;Weary, Jordan, & Hill, 1985) bestows value on internal causal explanations, and that persons who give internal explanations are accredited with that value by social evaluators. A social judgment norm thus permits members of the concerned collective to adopt upgrading self-presentation strategies.…”
Section: Normativenessmentioning
confidence: 98%
“…The social value attached to certain events may be transferred to the persons who bring about such events (or make such judgments), which is what one of the paradigms of the normative approach, the judge paradigm, is able to show. With this paradigm, it has been amply demonstrated that a norm of internality (Beauvois, 1984;Beauvois & Dubois, 1988;Dubois, 1994;Jellison & Green, 1981;Weary, Jordan, & Hill, 1985) bestows value on internal causal explanations, and that persons who give internal explanations are accredited with that value by social evaluators. A social judgment norm thus permits members of the concerned collective to adopt upgrading self-presentation strategies.…”
Section: Normativenessmentioning
confidence: 98%
“…These were as follows: Beck's Cognitive Triad (Beck, 1972), control over the outcomes of one's behavior (Deci & Ryan, 1985), the ability to detect cause and effect in one's world (Weary, Jordan, & Hill, 1985), selfesteem (Rosenberg, 1965), and anxiety.…”
Section: Formorethantwodecadespsychologistshavestudiedmentioning
confidence: 99%
“…According to Smith (1989), school, as an organizational structure, is influenced by what is valued in the society, as reflected by certain social judgment norms (Dubois, 2003). Among the different social judgment norms, the norm of internality, proposed by Jellison and Green (1981) and generalized by Beauvois (1984), is one of the most widely studied (Beauvois & Dubois, 1988;Dubois, 1994;Weary, Jordan, & Hill, 1985).…”
Section: Some Determinants Of Scholastic Judgmentsmentioning
confidence: 99%